JUMLAH ERITROSIT, KADAR HEMOGLOBIN, DAN NILAI HEMATOKRIT SAPI SIMPO YANG TERINFESTASI CACING SALURAN PENCERNAAN DI DESA LABUHAN RATU, KECAMATAN LABUHAN RATU, KABUPATEN LAMPUNG TIMUR - Tia Septiana, Siswanto, Madi Hartono, dan Sri Suharyati (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
This research was intended to determine the level of total erythrocytes, hemoglobin level, and hematocrit value of Simpo cattle which was infested with digestive worms. This research was conducted in Desember 2018 at Labuhan Ratu Village, East Lampung. The erythrocytes, hemoglobin, and hematocrit analysis were done in Veterinary Hall of Lampung. The research used Completely Randomized Design with 4 treatments and 4 replications. The treatment used were P0 (Simpo cattle without infested with the digestive worms), P1 (Simpo cattle were infested with Haemonchus sp.), P2 (Simpo cattle were infested with Paramphistomum sp.), and P3 (Simpo cattle were infested with Oesophagustomum sp.). The blood sample were used in this research from 16 Simpo cattle. Data were analyzed using variance analysis with significancy of 5%. The observed variables in this study were total erythrocytes, hemoglobin level, and hematocrit value. The results showed that the treatment of digestive worms infested was not different significantly (P<0.05) on total erythrocytes, hemoglobin level, and hematocrit value of Simpo cattle. Key words : Simpo cattle, Digestive worms, Erythrocytes, Hemoglobin , Hematocrit